Persepsi Mahasiswa Insitut Agama Islam Negeri Bone Terhadap Akun Instagram @Indonesiatanpapacaran - Muh. Aditiya Ramadhan; Saskiah Rismayani; Sri Wahyuningsih; Muh. Fadil Syahputra; Kurniati Abidin (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Dating relationships as a form of intimate personal relationships do not always go as expected. In fact, many cases show that these relationships can lead to discomfort and forms of violence, such as physical, psychological, sexual and financial abuse. This phenomenon has become one of the most discussed social issues, especially on social media. The Instagram account @indonesiatanpapacaran is present as a response to this issue, by voicing an invitation to abandon the practice of dating through moral and religious narratives. The existence of this account has led to various responses from the public, including students as a group of active social media users. This research aims to find out how students perceive the existence of the @indonesiatanpaparan account in the digital space. This research uses a descriptive qualitative approach with in-depth interview techniques and observation as data collection methods. The results showed that students gave diverse responses to the account, reflecting different attitudes, experiences, and perspectives in addressing the dating issues raised. This diversity also confirms that social media is a dynamic space that allows the formation of public opinion on complex social issues.